Can the Christian gospel speak to the experience of young people today? - Goodliff, Andy (Journal of youth and theology, 2004)
Soteriology is at the heart of all Christian ministry. Soteriology underpins all effective Christian youth ministry. In this article, Andy Goodliff explores traditional and contemporary models of soteriology in an attempt to find a theological language that speaks to young people today.